A system for high strain rate interruptible tensile tests - Thomas, Malcolm (Department of Mechanical Engineering, 2025)
The Split Hopkinson Pressure Bar (SHPB) is a widely used piece of equipment used for measuring a material's response to high strain rates. High strain rate data is critical for exhaustive characterisation, due to the sensitivity of materials to the rate at which they are strained. The principle limitation of conventional SHPB is that there is limited control of the ultimate deformation of specimens, because specimens are rarely recoverable after having undergone a single loading event. For this reason, microstructural investigations on SHPB specimens offer limited value, as the specimen was loaded repeatedly. In the MSc, a tensile SHPB (TSHB) was designed with momentum trapping to conduct interruptible tests on specimens. This configuration makes use of tandem momentum traps, allowing for the system to be fully trapped without the need for precisely preset gaps, or tight control over striker speed. A pull-off design of tubular tensile striker was used alongside the tandem momentum trapping, in a novel configuration allowing the input bar to remain supported over its entire length. The fir-tree design of dynamic tensile specimen fixture was utilised. Thorough preliminary measurements of the wave propagation properties of the hardware are taken. Strain gauge calibration tests were then conducted, followed by a rigorous commissioning process. This involved fine-tuning trap impedances and verification of the complex critical subsystems. As the commissioning process progressed, emergent flaws were rectified, and a standard operating procedure was established to ensure the reliable performance of said subsystems. The operation of the TSHB was demonstrated by a series of experiments on DOMEX 550 specimens. The recorded loading history is compared to the measured length of recovered specimens as verification of the interruptibility of tests using this apparatus. These specimens are also compared to those tested under the same conditions, but without the interruption, further demonstrating the effectiveness of the developed system.